Fast torque control and minimized sector-flux droop for constant frequency torque controller based DTC of induction machines - Alsofyani, Ibrahim Mohd; Bak, Yeongsu; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2019)
In this paper, two simple control methods are proposed for improving direct torque control (DTC) with a constant frequency torque controller (CFTC-DTC) in induction machines. The CFTC-DTC was initially introduced to reduce torque ripple and achieve constant switching frequency in inverters. However, when compared to the original DTC, the CFTC-DTC algorithm suffers from slow torque dynamic response owing to the selection of zero-voltage vectors during torque transient. In addition, when the motor operates at low speed, flux droop occurs at sector transitions, which leads to undesirable current distortions. The problem of flux droop occurs because of short-duty voltage cycles and small radial voltage components at low speeds. This paper has two main contributions-to eliminate zero-voltage vectors during torque dynamics in order to establish a fast torque response in the transient state, and to minimize the flux droop at the sector transitions by applying another triangular carrier and modifying the torque output in order to increase the duty voltage cycles at low motor speeds. A detailed analysis of the problems and proposed methods is presented. Experimental results are provided to validate the effectiveness of both proposed methods.
Keywords: Constant switching frequency; Current distortion; Direct torque control; Fast torque response; Flux regulation; Low speed; Simple control method; Zero voltage vectors; Direct torque control (DTC); fast torque dynamic; flux regulation; induction motor; low speed; torque control